THE WORKING OUT OF TECHNOLOGICAL PARAMETERS OF CITRON PECTIN PREPARATION FOR STABILIZATION OF IODIZED SOY-FATTY EMULSIONS - N. D. Zhmurina; T. A. Senkina; S. Y. Kobzeva; T. A. Shendakova; E. G. Merkulova; O. L. Ladnova (Современная наука и инновации)
The article presents research materials aimed at developing the technology of iodized soy-fat emulsions using citrus pectin as a stabilizer. The authors prove the expediency of its use in the production of emulsions. As a result of studying the stability and yield strength of exemplary emulsion, the optimal amounts of the stabilizer are determined.